Hemifacial Spasm Treatment and Its Perception in Traditional Chinese Medicine - มีศิลป์, เสาวลักษณ์; เสี่ยวผิง, เหวิน (Journal of Health Sciences and Wellness, 2018)
Hemifacial spasm (HFS) can be divided into two groups: symptomatic hemifacial spasm, disease with known cause that can be treated with surgery; and idiopathic hemifacial spasm. The cause of which is unknown and remains a problem in clinical practice. Botulinum toxin injection has been the most effective treatment option, but there are still side effects caused by this treatment. Traditional Chinese Medicine (TCM) has a variety of treatment options such as acupuncture, Tui na (Chinese massage), and Chinese herbal medicine. There is a lot of clinical evidence that clearly demonstrated its effectiveness, and at present TCM has become one of the best options for HFS treatment. This article will review the Traditional Chinese Medicine treatment options for HFS and its clinical researches.